Depth Contour Smoothing Based on the Fitting of Multi-Segment Bezier Curves. Issue 4 (4th July 2018) - Li, Jinghan; Wu, Fang; Gong, Xianyong; Du, Jiawei; Xing, Ruixing
ABSTRACT: To overcome smoothness inconsistencies in depth contours interpolated from sounding data, this paper proposes a smoothing method based on the fitting of multi-segment Bezier curves considering navigational safety. The basic principle of this method is the division of a generated depth contour into a series of bends categorized as either convex bends or concave bends. Different smoothing strategies are designed for different bends while considering the safety constraint. Convexity-preserving Bezier curves are used to fit convex bends. For concave bends, the line segment of the bend is utilized as a boundary to construct a control polygon within the interior of the bend, after which a Bezier curve is constructed based on the polygon. Experiments with real data are implemented, and the results are compared with those of other methods. The results show that the smoothing procedure for depth contours with angularities is effective and respects the safety constraint; moreover, the shape characteristics are preserved, and high positional accuracy is achieved. In addition, the proposed smoothing method is free of topological inconsistencies.